Competencies and (global) talent management - Machado, Carolina, 1965- (Springer, 2017)
This book covers the main issues on the study of competencies and talent management in modern and competitive organizations. The chapters show how organizations around the world are facing (global) talent management challenges and give the reader information on the latest research activity related to that. Innovative theories and strategies are reported in this book, which provides an interdisciplinary exchange of information, ideas and opinions about the workplace challenges.
Includes index.
Keywords: Personnel management.; Employee motivation.; Self-directed work teams.; elektronické knihy; electronic books